KAJIAN TRI HITA KARANA PADA PEMBERITAAN KOLOM TAKSU PORTAL BERITA ANTARA BIRO BALI - I Made Bagus Andi Purnomo (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The government is currently incessantly eradicating hoaxes that are widely circulated on social media. Hoax news is spread not only on media with maenstrems media background, but also sometimes on media with large platforms. Unfortunately, nowadays people are hard to tell which news is factual (real) and can educate and hoax (hoax). Previous research conducted by I Gede Riana (2011) entitled The Impact of Tri Hita Karana (THK) Culture Application on Entrepreneurship Orientation and Market Orientation and Its Consequences for the Business World (Study on Small and Medium Silver Businesses in Bali) in the form of the level of impact of THK culture application only and has not touched the realm of THK material sources in the form of books or reading sources in the form of news. Besides that the research of Dewa Nyoman Westika entitled Application of the Tri Hita Karana Concept in Housing Planning in Bali (2005) needs to be complemented by the carrying capacity of mass media content that provides news that contains elements of THK. Therefore, this study will attempt to assess the value of THK in reporting on one of the media in Bali. It is expected that the research conducted can provide information to the public about the content of THK values in the news on the News Agency portal between the Bali Bureau. Keywords: Study, Tri Hita Karana, Antara News Agency Portal